Water Stress Inhibits Germination While Maintaining Embryo Viability of Subtropical Wetland Seeds: A Functional Approach With Phylogenetic Contrasts - Bhatt, Arvind; Daibes, L. Felipe; Gallacher, David J.; Jarma-Orozco, Alfredo; Pompelli, Marcelo F. (Frontiers in Plant Science, 2022)
We investigate the effects of drought stress on the seed germination of species those occurred in wetland habitat. Germination percentage decreased with an increase of polyethylene glycol 6000 (PEG) concentration among the tested species. Moreover, germination parameters also varied significantly under different concentration of PEG, depending on species. Seeds were able to recover their germinability after alleviating the drought stress, although the germination recovery also vary from species to species. Our findings indicate that species specific variation in germination under drought stress and germination recovery after alleviating the drought stress.